Partisipasi Siswa Dalam Pelaksanaan Program Adiwiyata Dalam Membentuk Karakter Siswa Green School Islamic - Eka Sapitri; Isabella, Isabella; Doris Febriyanti (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to analyze the policies of the Ministry of Environment regarding student participation in the implementation of the Adiwiyata program in shaping environmentally caring character among students at the Ibnul Fallah Islamic boarding school in Bangsal Village, Pampangan District, Oki Regency. This program is expected to foster students' awareness of their surrounding environment. The research employs a qualitative approach, utilizing data collection methods through observation. The informants include the headmaster, deputy headmaster, secretary, teaching staff, students, and local community members. The collected data is analyzed through three stages: data reduction, data presentation, and conclusion drawing. This study uses the participation theory by Cohen Uphoff, which consists of four main indicators: 1) Decision-Making/Planning, 2) Implementation of the Adiwiyata program, 3) Benefits derived from implementation, and 4) Evaluation of implementation. The research results indicate that the implementation of the Adiwiyata program has been quite successful since January 2023. The program has brought benefits to the school, students, and the surrounding community in terms of environmental conservation. However, there are still several obstacles in the program's implementation, such as the distance of the operational location from the school. This study suggests the necessity of improving operational facilities for the program, such as providing simple transportation (bicycles) and facilities for laptop use, so that students can arrive at the location on time and participate effectively in ICT-related activities as part of their learning. The provision of these facilities would.